A Comprehensive Review on PBL and Digital PBL in Engineering Education - Status, Challenges and Future Prospects - Patnawar, Sneha T. (Journal of Engineering Education Transformations, 2025)
Problem-based learning (PBL) makes use of complex, real-world issues as the subject matter, and encourages students to develop problem-solving skills and learn concepts instead of just absorbing facts. The emergence of the concept of PBL in the digital learning context has received massive recognition and has thus, triggered debate among several scholars. Therefore as a prelude to analysis, the present study attempts to review the existing literature on PBL, particularly in the context of digital learning with respect to engineering education. It further attempts to discuss the ways for PBL implementation, its related challenges and future prospects, especially in the digital setting. The study adopted a systematic literature review wherein it selected relevant studies, articles and papers that broadly discussed the significance of the topics and evaluated information and data from the period starting from 2012 through 2021. A comprehensive review of the literature revealed that since digital PBL includes diverse and multiple 1 Sneha T. Patnawar Department of Biotechnology Engg., Kolhapur Institute of Technology’s College of Engineering(Autonomous), Kolhapur- 416234, snehakagale1@ gmail.com digital technology applications as part of traditional PBL it is more effective than the traditional form of learning and it is most widely used in engineering education as the aim of engineering education is to generate such students who are practically equipped with technical knowledge and considerably prepared with professional engineering skills. However, there exists a paucity of research on digital PBL which needs further analysis.